1995
DOI: 10.1111/j.1540-8191.1995.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Stentless Porcine Bioprostheses in the Treatment of Aortic Valve Infective Endocarditis

Abstract: Between January 1992 and June 1994, 23 patients underwent surgery for aortic valve endocarditis at the Department of Cardiovascular Surgery of the University of Verona; a subgroup of 10 patients underwent aortic valve replacement with a porcine stentless valve (Biocor LTDA n = 8; Toronto SPV n = 2). There were 7 males and 3 females with a mean age of 56.3 years (range, 36 to 73 years). Eight patients had active endocarditis and two had healed endocarditis. Nine patients had native valve in endocarditis, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…9 Recently, stentless porcine valves have been used to treat infectious endocarditis. 19,20 Santini and colleagues 19 reported a series of 10 cases of aortic valve infective endocarditis treated with porcine stentless valve (Biocor LTDA, Biocor Industriae e Pesquisa LtDa, Belo Horizonte, Brazil; Toronto SPV, St Jude Medical, Inc, St Paul, Minn). Our surgical strategy for managing complex aortic endocarditis is full root replacement with the Freestyle stentless valve after extensive de ´bridement of infected tissue, with closure of abscess as indicated.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…9 Recently, stentless porcine valves have been used to treat infectious endocarditis. 19,20 Santini and colleagues 19 reported a series of 10 cases of aortic valve infective endocarditis treated with porcine stentless valve (Biocor LTDA, Biocor Industriae e Pesquisa LtDa, Belo Horizonte, Brazil; Toronto SPV, St Jude Medical, Inc, St Paul, Minn). Our surgical strategy for managing complex aortic endocarditis is full root replacement with the Freestyle stentless valve after extensive de ´bridement of infected tissue, with closure of abscess as indicated.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…Full root replacement appears particularly advantageous in the treatment of acute infective endocarditis with a decrease in the incidence of postoperative paravalvular leaks and recurrent endocarditis [6,14,15]. In patients with aortic valve stenosis in combination with dilatation of the ascending aorta, valve replacement using a stentless xenograft and concomitant replacement of the aorta with a Dacron prosthesis seems to be an effective surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Regarding the resistance to infection, the superiority of the Freestyle stentless bioprosthesis over other stented bioprostheses or mechanical valves has not yet been demonstrated under an experimental analysis or clinical large-population study. Previously, Santini et al 14 suggested the efficacy of stentless porcine bioprosthesis (Biocor LTDA and Toronto SPV) in the treatment of 10 patients with aortic valve endocarditis. As for the Freestyle bioprosthesis, Katsumata et al 6 used it for three patients with active endocarditis who presented with aortic root abscess and partial or complete aorto left-ventricular discontinuity.…”
Section: Commentsmentioning
confidence: 99%